2012
DOI: 10.1038/nutd.2011.21
|View full text |Cite
|
Sign up to set email alerts
|

Appetite regulation and weight control: the role of gut hormones

Abstract: The overwhelming increase in the prevalence of overweight and obesity in recent years represents one of the greatest threats to the health of the developed world. Among current treatments, however, gastrointestinal (GI) surgery remains the only approach capable of achieving significant weight loss results with long-term sustainability. As the obesity prevalence approaches epidemic proportions, the necessity to unravel the mechanisms regulating appetite control has garnered significant attention. It is well kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
147
0
10

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(158 citation statements)
references
References 133 publications
(181 reference statements)
1
147
0
10
Order By: Relevance
“…It is tempting to speculate that the innate immune system could somehow react to metabolic changes by modulating the balance between orexygenic and anorexigenic signals in the hypothalamus (Perry and Wang, 2012;Sartin et al, 2011), and/or regulating the levels of lipomobilization and plasma NEFA, which are also sensed by TLR4 for further possible feedback regulations (Suganami et al, 2007).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…It is tempting to speculate that the innate immune system could somehow react to metabolic changes by modulating the balance between orexygenic and anorexigenic signals in the hypothalamus (Perry and Wang, 2012;Sartin et al, 2011), and/or regulating the levels of lipomobilization and plasma NEFA, which are also sensed by TLR4 for further possible feedback regulations (Suganami et al, 2007).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The use of ILJV provided a guide for the structural distinction between the peptide's helical region and dynamic tail region. The helical region (residues 14 (20,48). All restraints are detailed in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…hPP was the first member of the NPY family of peptides to be identified. It is secreted after food ingestion in proportion to its caloric content (14), and it promotes appetite suppression and inhibition of gastric emptying (15). This ligand was already found in ancient tetrapod evolution and appears to be one of the fastest developing peptides of the family (12).…”
mentioning
confidence: 99%
“…Peptides regulating food intake often act in concert or in series with other neurotransmitters to exert their actions (Perry and Wang, 2012). Nesfatin-1/NUCB-2 is colocalized with a number of hypothalamic peptides regulating food intake (Fort et al, 2008;Shimizu et al, 2009b;Maejima et al, 2009;Yoshida et al, 2010;Tan et al, 2011;Kerbel and Unniappan, 2012;GoebelStengel and Wang, 2013).…”
Section: Nesfatin-1/nucb-2 and Anorexigenic Effectmentioning
confidence: 99%
“…Nesfatin-1 injected intracerebroventricularly significantly decreased gastric emptying (García-Galiano et al, 2012). Goebel-Stengel and Wang (2012) showed that NUCB2/ nesfatin-1 immunoreactivity is distributed in mouse brain areas involved in the regulation of stress response and visceral functions activated by an acute psychological stressor suggesting that nesfatin-1 might play a role in the efferent component of the stress response.…”
Section: Introductionmentioning
confidence: 99%